MULTIDISCIPLINARY APPROACH IN EDUCATION AND HEALTH: BORBOLETANDO PROJECT - Nogueira , Teresinha de Jesus Araújo Magalhães; Ramos , Sandra Lima de Vasconcelos; dos Santos , Marilde Chaves; da Silva , Livia Fernanda Nery; Reis , Amada de Cássia Campos; Soares , Norma Patricya Lopes; Carvalhêdo , Josania Lima Portela; Cavalcante, Irlaine Cutrim Helal (Seven Editora, 2024)
This study presents an analysis of the "Borboletando Project: at home you can also learn!", focusing on the multidisciplinarity that involves the area of education, focused on health. The Project presents its relationship between health and education of the human being, in a virtual space. It aims to use playfulness through various resources such as the art of storytelling, music and animations produced in an artisanal way, integrated with digital technology in the continuum of informal education, enabling information and learning about the reality and imagination of children, meeting contemporary needs. DOI: https://doi.org/10.56238/sevened2024.037-026